1996
DOI: 10.1183/09031936.96.09091801
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index, age and upper airway measurements in snorers and sleep apnoea patients

Abstract: R Re el la at ti io on ns sh hi ip p b be et tw we ee en n b bo od dy y m ma as ss s i in nd de ex x, , a ag ge e a an nd d u up pp pe er r a ai ir rw wa ay y m me ea as su ur re em me en nt ts s i in n s sn no or re er rs s a an nd d s sl le ee ep p a ap pn no oe ea a p pa at ti ie en nt ts s ABSTRACT: Anatomical pharyngeal and craniofacial abnormalities have been reported using upper airway imaging in snorers with or without obstructive sleep apnoea (OSA). However, the influences of the age and weight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
119
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 38 publications
16
119
1
Order By: Relevance
“…11-14 The most common measurements used to compare the static morphology of the upper airway between OSA patients and healthy subjects (non-OSA) are the minimum surface area of the oropharyngeal region 15 and the anterior-posterior (AP) and lateral (L) dimensions of this area. [10][11]16 Other authors correlated OSA with the body mass index (BMI = kg/m 2 ) and many of them found a positive relationship between these two factors. 1,16-18 In addition to BMI it is also possible that the shape of the airway is a predictor of collapse.…”
Section: Introductionmentioning
confidence: 99%
“…11-14 The most common measurements used to compare the static morphology of the upper airway between OSA patients and healthy subjects (non-OSA) are the minimum surface area of the oropharyngeal region 15 and the anterior-posterior (AP) and lateral (L) dimensions of this area. [10][11]16 Other authors correlated OSA with the body mass index (BMI = kg/m 2 ) and many of them found a positive relationship between these two factors. 1,16-18 In addition to BMI it is also possible that the shape of the airway is a predictor of collapse.…”
Section: Introductionmentioning
confidence: 99%
“…According to the CT study performed by Enciso et al [10], men older than 57 years and individuals having narrow upper airway measurement have been identified as a high risk group for OSA. Mayer et al [21] has also reported an increase in the width of the oropharynx in OSA patients. The long and narrow airway had increased the frequency of airway collapse [10,21,36].…”
Section: Discussionmentioning
confidence: 92%
“…In the aetiology of OSA, some of the most important parameters are the airway volume, airway length and various anthropometric measurements [1,9,10,21,36]. According to the CT study performed by Enciso et al [10], men older than 57 years and individuals having narrow upper airway measurement have been identified as a high risk group for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe OSAS patients had bigger neck circumference than those in the control group. Mayer P et al [24] in a study to study the Relationship between body mass index, age and upper airway measurements in snorers and sleep apnoea patients have found out that the anatomy varies with BMI. To assess a possible sleeprelated breathing disorder subjects had complete polysomnography, cephalometry and upper airway computed tomography.…”
Section: Discussionmentioning
confidence: 99%